A new technique for ureteral resection to prevent urine dissemination and cancer seeding - Hayato Hoshina; Toru Sugihara; Masayuki Kurokawa; Kaori Endo; Ei‐ichiro Takaoka; Satoshi Ando; Haruki Kume; Tetsuya Fujimura (IJU Case Reports)
Introduction We describe a case in which robot‐assisted radical ureterectomy was performed for residual ureteral recurrence in a postoperative patient with renal pelvis cancer. Case presentation A 75‐year‐old woman underwent laparoscopic radical nephroureterectomy for left renal pelvic cancer at another hospital. During follow‐up, a papillary tumor was found in the bladder on cystoscopy, and a continuous tumor was found in the residual ureter on computed tomography. Robot‐assisted radical ureterectomy was performed in combination with transurethral resection of bladder tumors. To avoid urine spillage, bladder cuff excision was performed using a mechanical suture device while monitoring the interior of the bladder. Conclusion We developed a new technique for remnant ureteral resection using cystoscopy and a vascular stapler to prevent urine dissemination and cancer seeding.